Home-administered pre-surgical psychological intervention for knee osteoarthritis (HAPPiKNEES): study protocol for a randomised controlled trial - das Nair, Roshan; Anderson, P; Clarke, Simon P.; Leighton, P; Lincoln, Nadina; Mhizha-Murira, Jacqueline R.; Scammell, Brigitte E.; Walsh, David A. (BioMed Central, 2016)
Background: Knee replacement surgery reduces pain for many people with osteoarthritis (OA). However, surgical outcomes are partly dependent on patients’ moods, and those with depression or anxiety have worse outcomes. Approximately one-third of people with OA have mood problems. Cognitive behavioural therapy (CBT), a psychological therapy, is recommended by the National Institute for Health and Care Excellence for improving mood. However, evidence for the effectiveness of CBT before knee surgery in improving pain, mood, and quality of life following this surgery for people with knee OA is lacking. Methods/Design: This is a multi-centre, mixed-methods feasibility randomised controlled trial to compare treatment as usual (TAU) plus a brief CBT-based intervention with a TAU-only control, for people with knee OA. We will recruit 50 patients with knee OA, listed for knee replacement surgery, with high levels of distress (assessed using a mood questionnaire), and who consent to take part. Participants will be randomly allocated to receive TAU plus intervention or TAU. Up to 10 sessions of CBT will be offered on an individual basis by a psychologist. The assessments and interventions will be completed before surgery. Repeat assessments at 4 and 6 months after randomisation will be sent and received by post. Two patient-partners will conduct feedback interviews with some participants to assess what aspects of the intervention were helpful or unhelpful, the acceptability of randomisation, the experience of being in a control group, and the appropriateness of the measures used. Interviews will be audio-recorded, transcribed, and analysed using the framework approach. We will examine the feasibility and acceptability of patient-partners conducting the interviews by also interviewing the patient-partners. Discussion: Findings from this study will be used to design a definitive study that will examine the clinical and cost-effectiveness of the CBT intervention in improving patient outcomes following knee surgery. Trial Registration: Current Controlled Trials ISRCTN80222865; Date: 19 June 2014